Pemanfaatan program CSR perusahaan untuk pemberdayaan perekonomian masyarakat Kabupaten Pelalawan di masa pandemi Covid-19 - Andrew Shandy Utama (Unri Conference Series: Community Engagement, 2020)
The Covid-19 pandemic that hit Riau Province had an impact on the economy of the community, including the people of Palas Village. Apart from expecting financial assistance from the government, one of the opportunities that the Palas Village community can take advantage of to develop the village economy is to take advantage of the CSR programs of companies operating in Pelalawan Regency. This community service aims to explain the use of the company's CSR program to empower the community's economy during the Covid-19 pandemic. The method of implementation used in community service activities uses the lecture method accompanied by direct dialogue with the community. Based on Article 74 of Law Number 40 of 2007 concerning Limited Liability Companies, it is stated that companies that carry out their business activities in the field of natural resources and / or fields related to natural resources are required to carry out CSR. The CSR program of PT RAPP that can be used by the people of Palas Village to build their economy is the Integrated Farming System program and the UMKM program. Before being given legal counseling, only 17.5% of the 20 participants knew the law regarding CSR. After being given legal education, there was an increase to 75% of the 20 participants who answered correctly. This means that this community service activity has succeeded in increasing the understanding of the Palas Village community.